Positioning Rural Tourism: Perspectives from the Local Communities - May-Chiun, Lo; Abang Azlan, Mohamad; Peter, Songan; Alvin Wee, Yeo (International Journal of Trade, Economics and Finance, 2012)
Malaysian rural tourism is composed of a large number of rural communities, each with distinct and varied assets. Within Malaysia, it is noticeably that tourism demand drivers play an important part in generating trips to rural tourism areas. Rural tourism enables tourists to reunite with nature and the culture of the destinations, and that it contributes to the economic and social recovery of the rural areas, as well as to the conservation of the environment and the spreading of local cultures. There are significant strengths and potential opportunities available to rural tourism marketing efforts. Ecotourism has been actively promoted by governments as well as the industry, without an overall effective strategy, successfully protected area management plans and without consultation or inclusion of local communities. Hence, the purpose of this research is to conduct an analysis based on the existing tourism industry in Bario by examining the impact of economics, environmental, social and cultural factors of the tourism industry on the local communities in Bario. The findings suggested that the tourism industry has created a significant impact on the cultural aspect of local communities. Implications of these findings are discussed further.